Overview of Chatbots with special emphasis on artificial intelligence-enabled ChatGPT in medical science - Chakraborty, Chiranjib; Pal, Soumen; Bhattacharya, Manojit; Dash, Snehasish; Lee, Sang-Soo (Frontiers in Artificial Intelligence, 2023)
The release of ChatGPT has initiated new thinking about AI-based Chatbot and its application and has drawn huge public attention worldwide. Researchers and doctors have started thinking about the promise and application of AI-related large language models in medicine during the past few months. Here, the comprehensive review highlighted the overview of Chatbot and ChatGPT and their current role in medicine.Firstly, we discussed the general idea of Chatbots, evolution, architecture, and medical use.Secondly, we discussed ChatGPT, where we illustrated its application in medicine, architecture and training methods, medical diagnosis and treatment, other research ethical issues, and a comparison of ChatGPT with other NLP models. The article also discussed the limitations and prospects of ChatGPT. In the future, these large language models and ChatGPT will have immense promise in healthcare. However, more research is needed in this direction.